2008
DOI: 10.1192/bjp.bp.107.044974
|View full text |Cite
|
Sign up to set email alerts
|

Severity of depression and risk for subsequent dementia: cohort studies in China and the UK

Abstract: Only the most severe syndromes and cases of depression are a risk factor for dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 25 publications
9
88
2
1
Order By: Relevance
“…11 Our findings add to the existing literature by demonstrating a monotonic increase in dementia risk as a function of EDS in a community sample. In contrast to a previous report of increased dementia risk only in severe depression, 26 we observed an increased risk in individuals whose CES-D scores were sufficiently elevated to be considered clinically significant but whose symptoms were not severe enough to warrant hospitalization, and for most participants, did not result in treatment of any kind.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofcontrasting
confidence: 55%
“…11 Our findings add to the existing literature by demonstrating a monotonic increase in dementia risk as a function of EDS in a community sample. In contrast to a previous report of increased dementia risk only in severe depression, 26 we observed an increased risk in individuals whose CES-D scores were sufficiently elevated to be considered clinically significant but whose symptoms were not severe enough to warrant hospitalization, and for most participants, did not result in treatment of any kind.…”
Section: Figure 2 Kaplan-meier Survival Curve Of Time To Incidence Ofcontrasting
confidence: 55%
“…Depression was associated with the risk of AD in many previous studies [44,45,46]. Depression is more prevalent in elderly Korean persons than in elderly persons in other Asian and Western countries [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the depression-conferred risk of AD may not be uniform across the severity of depression. Chen et al [46] reported that incident dementia was associated with the most severe depressive syndromes but not with mild depression. Similarly, the risk of AD increased with increased severity of depression in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies it was revealed that marriage has been shown to be a protective factor against depression in the elderly 23,8 . The findings of this study are similar to other studies conducted in health clinics in Malaysia 24 .…”
Section: Socio-demographic Correlates and Depressionmentioning
confidence: 99%